COVID-19 vaccine barriers among pregnant and lactating refugee women: a case study - Williams, Elisabeth; Azugbene, Ehiremen; Lozano, Fernanda; Liu, Li; Patton, Tatiana; Nizigiyimana, Jeanne; Johnson-Agbakwu, Crista; Koskan, Alexis M. (Frontiers in Public Health, 2025)
IntroductionPregnant and lactating refugee women rank among the groups least likely to vaccinate against COVID-19. This qualitative study explores their reasons for COVID-19 vaccine hesitancy.MethodsBetween June 2023 and January 2024, cultural health navigators (CHNs) employed by one hospital system conducted in- depth interviews with COVID-19 vaccine-hesitant pregnant and lactating refugee women from five language groups (Arabic, Burmese, Kinyarwanda, Somali, and Swahili). The team also conducted in-depth interviews and a focus group with the five CHNs to further understand community-level factors influencing refugee women's vaccine hesitancy. All qualitative data were analyzed using inductive thematic analysis.ResultsParticipants expressed fear of long-term health effects, especially of becoming infertile or of their babies dying, as the primary reasons for not vaccinating. Others reported their perceptions that COVID-19 is no longer a significant health concern. CHNs described the role of social media in spreading misinformation about the vaccine, leading to vaccine hesitancy. Some unanticipated themes that emerged included the role of men in vaccine decision-making and the fear of disrespecting their healthcare provider by declining the vaccine.DiscussionStudy results indicated the need to continue to combat misinformation about the COVID-19 vaccine amongst pregnant and lactating refugee women and the need to take a community-based approach to increase vaccine trust. For example, community health workers or CHNs can provide patient education to increase vaccine trust. Trusted civil organizations could disseminate messages targeting vaccine misinformation spread on social media platforms. Additionally, digital storytelling in refugees' native languages can be a helpful dissemination tool to increase vaccine education and combat misinformation and vaccine hesitancy.